2019
DOI: 10.1002/pat.4777
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Nucleation and Crystallization in PLA/CNT Composites via Disperse Orange 3 with Corresponding Improvement in Nanomechanical Properties

Abstract: The potential for the material property improvement through the addition of carbon nanotubes (CNTs) in composite materials is often limited due to CNT agglomeration.In this work, Disperse Orange 3 (DO3) was investigated to determine its effectiveness in dispersing CNTs in a poly (lactic acid) (PLA) matrix. First, adsorption studies of DO3 onto CNTs were performed to determine the appropriate amount of DO3 to add so that the CNT surface will be nearly saturated with DO3 while limiting the excess DO3 dissolved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Nanoindentation is a non-destructive tool for testing thin films and surface mechanical properties of a wide range of materials including polymers [ 24 , 25 , 26 , 27 ]. In this study, nanoindentation technique was employed to measure micromechanical properties of the PLA/PLA-CNT thin films before and after degradation.…”
Section: Methodsmentioning
confidence: 99%
“…Nanoindentation is a non-destructive tool for testing thin films and surface mechanical properties of a wide range of materials including polymers [ 24 , 25 , 26 , 27 ]. In this study, nanoindentation technique was employed to measure micromechanical properties of the PLA/PLA-CNT thin films before and after degradation.…”
Section: Methodsmentioning
confidence: 99%
“…12 Extensive research has been done for improving as well as tuning the physical and mechanical properties of PLA, which usually involves the addition of nanoparticles or blending with another polymer. [13][14][15][16][17][18] In a research conducted by Kim et al, they found that upon adding a small amount of carbon nanotubes/graphene oxide hybrid nanoparticle system, the permeability of oxygen into PLA film would be greatly reduced. 5 Urquijo et al observed that the percentage of gas penetration into a blend of PLA and poly (ε-caprolactone) could significantly be reduced by adding an appropriate amount of nanoclay.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has been done for improving as well as tuning the physical and mechanical properties of PLA, which usually involves the addition of nanoparticles or blending with another polymer 13–18 . In a research conducted by Kim et al, they found that upon adding a small amount of carbon nanotubes/graphene oxide hybrid nanoparticle system, the permeability of oxygen into PLA film would be greatly reduced 5 .…”
Section: Introductionmentioning
confidence: 99%